Disputing strategies in medieval Scandinavia - Esmark, Kim; Hermanson, Lars, 1967-; Orning, Hans Jacob; Vogt, Helle (Medieval law and its practice, 2013)
The book discusses how conflicts were handled in medieval Scandinavia. Using practice as analytical concept, the authors explore law and litigation in conjunction with non-formal legal proceedings such as out-of-court mediation, rituals, emotional posturing, and feuding.